2016
DOI: 10.1063/1.4967797
|View full text |Cite
|
Sign up to set email alerts
|

Water self-diffusivity confined in graphene nanogap using molecular dynamics simulations

Abstract: Fundamental understanding of water confined in graphene is crucial to optimally design and operate sustainable energy, water desalination, and bio-medical systems. However, the current understanding predominantly remains in the static properties near the graphene surfaces. In this paper, a key water transport property, i.e., self-diffusivity, is examined under confinement by various graphene nanogap sizes (L z ¼ 0.7-4.17 nm), using molecular dynamics simulations with various graphene-water interatomic potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
4
6
0
Order By: Relevance
“…The high diffusivity in the two systems was also similar to results from previous studies . It was found that 2D diffusivity of water molecules confined in graphene nanogap was significantly higher than that in bulk water . Interestingly, there seems to be a similar critical pore diameter (1.36–1.63 nm) for water diffusion in carbon nanotubes (CNTs).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The high diffusivity in the two systems was also similar to results from previous studies . It was found that 2D diffusivity of water molecules confined in graphene nanogap was significantly higher than that in bulk water . Interestingly, there seems to be a similar critical pore diameter (1.36–1.63 nm) for water diffusion in carbon nanotubes (CNTs).…”
Section: Resultssupporting
confidence: 87%
“…36 It was found that 2D diffusivity of water molecules confined in graphene nanogap was significantly higher than in bulk water. 53 Interestingly, there seems to be a similar critical pore diameter (1.36 ~1.63 nm) for water diffusion in carbon nanotubes (CNTs). By comparing results from water diffusion in CNTs with the same diameters and at the same temperature (results of CNTs from Farimani et al 42 , Zheng et al 43 , Köhler et al 54 , Won et al 55 ), the D z of water molecules was also close to bulk water in the CNTs with diameter larger than 1.36 nm, otherwise significantly lower in smaller CNTs (Figure 3a, data points from references).…”
Section: Resultsmentioning
confidence: 99%
“…Density profiles for corresponding ε c-o values in Fig. 8, which are similar to that of another report [34], displays this increasing water molecule density near the interfacial regions that enable for enhanced heat transfer at higher interaction strengths. As system size increases with channel height from H = 4.0 to 8.0 nm, convection performance displays enhancement with an increase towards that of macroscale behavior from Nu D,fd = 0.…”
Section: Fully-developed Heat Transfersupporting
confidence: 84%
“…Water molecules are kept rigid, maintaining bond length (O-H) and angle (H-O-H) constant using the SHAKE algorithm [33]. Liquid water molecules corresponding to a density of ρ = 1000 kg/m 3 are placed in-between the two nanochannel walls; an additional 0.25 nm of spacing between the block of liquid water molecules and each nanochannel surface is added so to account for the water unoccupied volume [34][35][36].…”
Section: Simulation Detailsmentioning
confidence: 99%
“…The OG structure is similar to a Janus pore or interface, , where the fluid is confined between two surfaces, one hydrophilic and the other hydrophobic. Deposition rates during vacuum filtration have been shown to influence the interlayer stacking, with slower rates giving rise to structures assembled with a larger number of G–G and O–O interfaces, enabling higher water permeability through the G–G regions . For a given interlayer spacing, the extent of occurrences of these different interfaces is expected to determine the water transport in these systems.…”
Section: Introductionmentioning
confidence: 99%